Oral health care value in disadvantage areas of south lampung regency, lampung province: Study Observational - Al Risky, Sava; Zubaedah, Cucu; Hamdani, Ardena Maulidia (Padjadjaran Journal of Dental Researchers and Students, 2026)
ABSTRACTIntroduction: Dental and oral health is one of the parts that must be kept clean, because through these tissues various microorganisms can enter. Oral health care plays an important role in maintaining a person's well-being and quality of life. In some underdeveloped areas such as South Lampung Regency, Lampung Province, efforts to maintain oral health are still a serious problem for the region, so it is necessary to know the value of maintaining oral health in the community. Methods: This research is a descriptive study using a questionnaire survey method. The sampling technique of this study used a simple random sampling method, with a total of 97 adult respondents who had settled in South Lampung Regency, Lampung Province and were willing to be research subjects. This research instrument is a questionnaire with a total of 41 questions that have passed the validity and reliability tests.  Results: The value of oral health maintenance in the good category was 47.3%, the community was in the good category in the dimension of oral health maintenance actions as much as 50.5% and the statement of distance from oral health services which stated that it was close was 10.3%. The low dimensions of the oral health maintenance value variable are due to factors of education level and socio-economic conditions and which play a role in the community of disadvantaged areas of South Lampung Regency, Lampung Province regarding the importance of oral health maintenance, as well as the absence of affordable and easily accessible health facilities for the community. Conclusion: The value of maintaining oral health of the people of South Lampung Regency, Lampung Province obtained a value of 36.03%, and fell into the low category.KEYWORDS: Oral health, health knowledge, attitudes, practice, dental care, health services accessibility, public healthNilai pemeliharaan kesehatan gigi dan mulut pada masyarakat daerah tertinggal kabupaten lampung selatan, provinsi lampung: Studi observasionalABSTRAKPendahuluan: Kesehatan Gigi dan mulut harus dipertahankan tingkat kebersihannya, karena melalui jaringan ini berbagai macam mikroorganisme dapat masuk ke dalam tubuh. Perawatan kebersihan gigi dan mulut berperan penting dalam menjaga kesejahteraan dan kualitas hidup seseorang. Beberapa wilayah tertinggal seperti Kabupaten Lampung Selatan, Provinsi Lampung, upaya dalam menjaga kesehatan gigi dan mulut masih terbatas. Tujuan penelitian ini adalah untuk mengetahui nilai pemeliharaan kesehatan gigi dan mulut pada masyarakat Kabupaten Lampung Selatan. Metode: penelitian deskriptif dengan metode survei kuisioner dan metode simple random sampling, dengan responden sejumlah 97 orang dewasa yang telah menetap di Kabupaten Lampung Selatan dan bersedia sebagai subjek penelitian. Instrumen penelitian berupa kuesioner dengan total 41 butir pertanyaan yang telah melewati uji validitas dan reliabilitas.  Hasil: Nilai manfaat pengetahuan pemeliharaan kesehatan gigi dan mulut kategori rendah 47,03%, masyarakat dalam kategori rendah pada dimensi tindakan pemeliharaan kesehatan gigi dan mulut 50,5% dan pernyataan jarak pelayanan kesehatan gigi dan mulut yang menyatakan dekat 10,3%. Rendahnya dimensi pada variabel nilai pemeliharan kesehatan gigi dan mulut tersebut dikarenakan faktor tingkat pendidikan, kondisi sosial ekonomi, tidak adanya fasilitas kesehatan yang terjangkau dan mudah diakses bagi masyarakat. Simpulan: Nilai pemeliharaan kesehatan gigi dan mulut masyarakat Kabupaten Lampung Selatan, Provinsi Lampung sebesar 36,03%, dan masuk kedalam kategori rendah.KATA KUNCI: Kesehatan gigi dan mulut, pengetahuan, sikap, dan praktik kesehatan, pelayanan perawatan gigi, aksesibilitas pelayanan kesehatan, kesehatan masyarakat